2018
DOI: 10.1002/fsn3.748
|View full text |Cite
|
Sign up to set email alerts
|

Development of value‐added nutritious crackers with high antidiabetic properties from blends of Acha (Digitaria exilis) and blanched Pigeon pea (Cajanus cajan)

Abstract: Pigeon pea was treated by blanching and used to supplement acha flour for the development of functional cracker biscuits. The flour ratios for acha and pigeon pea were 100:0 (ACC), 80:20 (APC1), and 70:30 (APC2), respectively. The developed cracker biscuits were evaluated for chemical acid compositions, antioxidant, as well as antidiabetic properties. Protein contents of the formulated crackers increased with increase in supplementation with pigeon pea flour. The antinutrient content of the formulated snack wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
47
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(60 citation statements)
references
References 39 publications
9
47
2
2
Order By: Relevance
“…The total contents of the activity‐associated amino acids in pigeon pea protein was 32%, which was similar to the amounts in the hydrolysates, PepH (35%), PapH (32%), and TheH (33%). Compared to a previously reported amino acid composition (Olagunju et al, , ), the pigeon pea protein in our study had higher amounts of Pro and Val, and lower amounts of Leu and Phe, although the total composition of the activity‐related amino acids are similar. Despite the similarity, particular amino acid composition of the hydrolysates in our study were different (e.g., PapH > PepH > TheH for Pro content), possibly due to the specificity of proteases used in hydrolyzing the pigeon pea proteins.…”
Section: Resultscontrasting
confidence: 93%
See 2 more Smart Citations
“…The total contents of the activity‐associated amino acids in pigeon pea protein was 32%, which was similar to the amounts in the hydrolysates, PepH (35%), PapH (32%), and TheH (33%). Compared to a previously reported amino acid composition (Olagunju et al, , ), the pigeon pea protein in our study had higher amounts of Pro and Val, and lower amounts of Leu and Phe, although the total composition of the activity‐related amino acids are similar. Despite the similarity, particular amino acid composition of the hydrolysates in our study were different (e.g., PapH > PepH > TheH for Pro content), possibly due to the specificity of proteases used in hydrolyzing the pigeon pea proteins.…”
Section: Resultscontrasting
confidence: 93%
“…Due to its physicochemical properties, pigeon pea flour has been used to enhance the nutritional value of wheat‐based baked goods (Gbenga‐Fabusiwa, Oladele, Oboh, Adefegha, & Oshodi, , ; Okpala & Okoli, ; Rampersad, Badrie, & Commissiong, ). Moreover, baked products formulated with pigeon pea flour are reported to have beneficial glycemic control and antidiabetic properties, which suggests potential use in managing type 2 diabetes mellitus (T2DM) (Gbenga‐Fabusiwa et al, ; Olagunju, Omoba, Enujiugha, & Aluko, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cracker White fonio Blanched pigeon pea flour (up to 30%) and fonio flour mixtures were made into crackers. Increasing pigeon pea flour concentration increased the in vitro antioxidant activities and the concentrations of methionine and lysine of the crackers, while decreasing the expected glycemic index Olagunju et al, 2018 Biscuit White fonio Fonio flour (50% to 100%) was partially replaced by unripe plantain (0% to 10%) and bambara nut (0% to 40%) flour to make biscuits. Biscuits made up of 70% or 80% fonio, 10% plantain, and 10% or 20% bambara nut had acceptable sensory quality.…”
Section: Fonio Type Major Findings Referencesmentioning
confidence: 99%
“…Fonio and fonio starch have been used in various food and nonfood applications (Table 2). Food applications include producing sprouts and malts (Ayo, Agbatutu, & Iribom, 2019; Lasekan, Salva, & Abbas, 2010; Nzelibe & Nwasike, 1995; Nzelibe, Obaleye, & Onyenekwe, 2000), gluten free drinks (Badejo et al., 2017), infant weaning and children's foods (Agbede, Omotoso, Oloruntola, Ayeni, & Aletor, 2019; Sosanya, Nweke, & Ifitezue, 2018), breakfast cereals (Mbaeyi‐Nwaoha & Uchendu, 2016), nonwheat pasta, noodles, porridge, puddings, crackers, biscuits and cookies, cakes, and sourdough breads (Ayo & Ayo, 2018; Ayo et al., 2019; Chinma, Ihekoronye, Mukoro, & Eke, 2015; Coda et al., 2010; Edema, Emmambux, & Taylor, 2013; McWatters, Ouedraogo, Resurreccion, Hung, & Phillips, 2003; Meli et al., 2013; Ogori, Uzor, Hleba, Císarová, & Glinushkin, 2020; Olagunju, Omoba, Enujiugha, & Aluko, 2018; Raji, Nassam, Abolaji, Ayorinde, & Raji, 2018; Umerie & Umeh, 2016). From the results summarized in Sections 2 and 3, it is concluded that fonio grain and flour do not contain gluten‐type protein for desired rheology for a range of bakery products.…”
Section: Food and Other Applications Of Fonio And Fonio Componentsmentioning
confidence: 99%